흑색종 세포증식 저해효능의 새로운 Benzaminoquinoline 유도체의 합성 - 남봉수; 유경호 (한국응용과학기술학회, 2009)
Melanoma is the most serious type of skin cancer as a malignant tumor of melanocytes. In this work, the syntheses of a novel series of benzaminoquinoline derivatives 1a-c and their antiproliferative activities against A375 human melanoma cell line were described. All the compounds (IC50 = 0.78-1.02 μM) showed superior antiproliferative activities to Sorafenib (IC50 = 5.58 μM) as a reference compound. These results suggested that benzaminoquinoline derivatives have potentials as a therapeutic agent for the treatment for melanoma.